Using The Flexible Analytic Hierarchy Process Method to Solve The Emergency Decision-Making of Public Health Emergency of International Concern (PHEIC) - Chung, Hsiang-Yu; Chang, Kuei Hu (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
The occurrence of a public health emergency of international concern (PHEIC) can lead to massive deaths, economic recession, and changes in the lifestyles of people in various countries. Addressing the problem of a public health emergency involves multiple experts and criteria, making it a multi-expert and multi-criteria decision-making problem. The assessment information of the criteria simultaneously includes complete, incomplete and hesitant fuzzy linguistic information in PHEIC problems. However, typical calculation methods cannot process the incomplete information and hesitant fuzzy linguistic information associated with PHEIC problems. In order to overcome these issues, this paper proposed a novel flexible AHP method to solve PHEIC problems. A numerical case study on public health emergency decision-making for COVID-19 was adopted to verify the effectiveness and correctness of the proposed flexible analytic hierarchy process (AHP) method. The numerical simulation results were also compared with the simple additive weighting (SAW) method, the traditional AHP method, the fuzzy set method, and the fuzzy AHP method. The simulation results show that the proposed method can provide a more reasonable and flexible decision analysis.